Role of Nanomedicines in Delivery of Anti-Acetylcholinesterase Compounds to the Brain in Alzheimer’s Disease - Z. Ahmad, Mohammad; Ahmad, Javed; Amin, Saima; Rahman, Mahfoozur; Anwar, Mohammad; Mallick, Neha; J. Ahmad, Farhan; Rahman, Ziyaur; A. Kamal, Mohammad; Akhter, Sohail (CNS & Neurological Disorders - Drug Targets, 2014)
Alzheimer's disease (AD) is a multifarious progressive neuro-degenerative state among elders. Potentiation of central cholinergic activity by using acetylcholinesterase inhibitors (AChEI) is considered as one of the major pharmacological means for the management of AD. Investigation in the past and the rest decades revealed that many drugs with anti-AD activity, including the AChEI have been discovered from natural and synthetic origin but getting success in their brain delivery is still limited. However, barriers like blood-brain barrier, blood-cerebrospinal fluid barrier and p-glycoproteins restrict the effective and safe drug delivery to the brain in patients with AD. Advancement in nanotechnology-based drug delivery systems over the last decade exemplifies the effective drug delivery and targeting to the brain with controlled rate in various diseases including AD. Till recently, diverse kinds of nanomedicines for targeting of the anti-AD drugs in brain are being studied. In this review, we have highlighted the recent progress in AChEI, challenges in their effective brain delivery (physicochemical properties and biological barriers) and possible nanotechnology-based strategies that can deliver drugs across the CNS barriers during AD.
Keywords: donepezil